Directing Multivalent Aptamer‐Receptor Binding on the Cell Surface with Programmable Atom‐Like Nanoparticles. Issue 18 (9th March 2022) - Guo, Linjie; Zhang, Yueyue; Wang, Yue; Xie, Mo; Dai, Jiangbing; Qu, Zhibei; Zhou, Mo; Cao, Shuting; Shi, Jiye; Wang, Lihua; Zuo, Xiaolei; Fan, Chunhai; et al.
Abstract: Multivalent interactions of biomolecules play pivotal roles in physiological and pathological settings. Whereas the directionality of the interactions is crucial, the state‐of‐the‐art synthetic multivalent ligand–receptor systems generally lack programmable approaches for orthogonal directionality. Here, we report the design of programmable atom‐like nanoparticles (aptPANs) to direct multivalent aptamer–receptor binding on the cell interface. The positions of the aptamer motifs can be prescribed on tetrahedral DNA frameworks to realize atom‐like orthogonal valence and direction, enabling the construction of multivalent molecules with fixed aptamer copy numbers but different directionality. These directional‐yet‐flexible aptPAN molecules exhibit the adaptability to the receptor distribution on cell surfaces. We demonstrate the high‐affinity tumor cell binding with a linear aptPAN oligomer (≈13‐fold improved compared to free aptamers), which leads to ≈50 % suppression of cell growth. Abstract : DNA framework‐based programmable atom‐like nanoparticles (aptPANs) and their assemblies with fixed aptamer copy numbers but different directionality were designed. These are employed to direct multivalent aptamer–receptor binding on the cell membrane interface. The directional‐yet‐flexible aptPAN molecules exhibit the adaptability to the receptor distribution on cell surfaces and thus high affinity against target tumor cells.